2022
DOI: 10.3389/fpls.2022.814620
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Repetitive DNA in Saccharum officinarum and Saccharum spontaneum by Genome Sequencing and Cytological Assays

Abstract: In most plant species, DNA repeated elements such as satellites and retrotransposons are composing the majority of their genomes. Saccharum officinarum (2n = 8x = 80) and S. spontaneum (2n = 40–128) are the two fundamental donors of modern sugarcane cultivars. These two species are polyploids with large genome sizes and are enriched in repetitive elements. In this work, we adopted a de novo strategy to isolate highly repetitive and abundant sequences in S. officinarum LA Purple and S. spontaneum SES208. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The above-mentioned genera, known for their high degree of chromosomal diversity and complexity, are among the most extensively studied groups in orchid cytogenetics [13][14][15][16][17][18][19][20][21][22][23][24]. These studies have revealed significant variation among species and lineages in the distribution and abundance of repetitive DNA, which may reflect different modes of chromosomal evolution, including genome duplication and rearrangement [25]. Studies of orchid cytogenetics employ various techniques to analyze chromosome structure, behavior, and function.…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned genera, known for their high degree of chromosomal diversity and complexity, are among the most extensively studied groups in orchid cytogenetics [13][14][15][16][17][18][19][20][21][22][23][24]. These studies have revealed significant variation among species and lineages in the distribution and abundance of repetitive DNA, which may reflect different modes of chromosomal evolution, including genome duplication and rearrangement [25]. Studies of orchid cytogenetics employ various techniques to analyze chromosome structure, behavior, and function.…”
Section: Introductionmentioning
confidence: 99%